Warriors of Ethiopia Ethiopian National Missionaries : heroes of the Gospel in the Omo River Valley - McLellan, Richard J. (Eastwood, NSW self-published, 2006)
A series of biographies of Ethiopian national missionaries
Donated and signed by the author.
Keywords: Missionaries -- Ethiopia